1994
DOI: 10.1037/0021-843x.103.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Personality and disinhibitory psychopathology: Alcoholism and antisocial personality disorder.

Abstract: We discuss the relation between personality factors and two adult forms of disinhibitory psychopathology--alcohol abuse or dependence and antisocial personality disorder. First, we briefly review various methodological issues relevant to research in this area. Next, we review empirical findings relating three broad-band personality trait dimensions neuroticism/emotionality, impulsivity/disinhibition, extraversion/sociability) to both alcohol abuse and dependence and antisocial personality disorder. Finally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
471
6
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(520 citation statements)
references
References 72 publications
34
471
6
9
Order By: Relevance
“…Impulsivity is thought to contribute to the risk of behavioral disinhibition under alcohol (Fillmore, 2007;Finn et al, 1994;Sher and Trull, 1994). Participants rated 30 different statements (e.g., "I do things without thinking") in terms of how typical each statement is for them on a 4-point Likert scale ranging from Rarely/Never to Almost Always/Always.…”
Section: Subjective Intoxication and Perceived Ability To Drive-partimentioning
confidence: 99%
“…Impulsivity is thought to contribute to the risk of behavioral disinhibition under alcohol (Fillmore, 2007;Finn et al, 1994;Sher and Trull, 1994). Participants rated 30 different statements (e.g., "I do things without thinking") in terms of how typical each statement is for them on a 4-point Likert scale ranging from Rarely/Never to Almost Always/Always.…”
Section: Subjective Intoxication and Perceived Ability To Drive-partimentioning
confidence: 99%
“…There is abundant evidence that alcohol dependence is a clinically heterogeneous disorder, varying in its age of onset, prevalence by gender, developmental course, and severity [Sher and Trull, 1994;Hill, 1995bHill, , 2000Finn et al, 1997;Hill and Yuan, 1999]. As in all studies of complex diseases, defining phenotypes that accurately reflect the underlying genetic susceptibility is critical for uncovering susceptibility genes.…”
Section: Introductionmentioning
confidence: 99%
“…Personality variation has also been implicated in the diathesis for alcohol dependence. Several characteristics have been suggested including negative affectivity and neuroticism [see Sher and Trull, 1994 for review], alienation [Hill et al, 1990b], and disinhibition/impulsivity [Sher et al, 1991] in offspring of alcoholics. We have found higher scores on the extraversion scale of the Eysenck Personality Inventory (EPI) predicts adolescent age of onset to begin regular drinking among high-risk offspring [Hill and Yuan, 1999;Hill et al, 2000b].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, impulsivity was distinct from sensationseeking, thus failing to support any suggestion that impulsivity was intrinsically related to this concept (e.g. Acton, 2003;Depue & Collins, 1999;Kelly et al, 2006;Moeller et al 2002;Sher & Trull, 1994;Zuckerman et al, 1993) and/or was an adult-form of sensation-seeking (Clayton, Segress & Caudill, 2007). Thus, in samples where there are known to be increased levels of sensation-seeking and impulsivity (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Acton, 2003;;Ersche, et al, 2010;Moeller et al 2002), openness to experience and extraversion (Grekin, Sher & Wood, 2006), with considerable cross-over across these constructs (Depue & Collins, 1999;Kelly et al, 2006;Sher & Trull, 1994;Zuckerman et al, 1993). For example, some researchers have suggested that extraversion is an indirect test of sensation-seeking (Sher & Trull, 1994), with impulsivity a reconceptualised 'adult' form of sensation-seeking (Clayton, Segress & Caudill, 2007). This poses the question as to whether these constructs are distinct, or if they are in fact best described as a single more unified personality concept of particular relevance to substance use.…”
mentioning
confidence: 99%